PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA SISWA KELAS V SEKOLAH DASAR KECAMATAN PASIR PENYU - Mulyani, Eva Astuti (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2016)
Implementation of Cooperative Learning Model Type of Jigsaw to Improve Mathematics Learning Outcomes in Fifth Grade Students of Elementary School, Pasir Penyu. This study aims to improve learning outcomes math class V students of State Elementary School 012 Candirejo Pasir Penyu through the implementation of cooperative learning model type of Jigsaw. Subject of this research are students in 5th grade 012 Candirejo public elementary school academic year 2011/2012, the number of students 30 people, consisting of 19 male students and 11 female students. The research instrument used is the test sheet of result of learning mathematics , Observation Sheet Activities Teacher and Student. Technique of collection and analysis of data obtained from the descriptive analysis of the activities of teachers, student activities, and the results of students' mathematics learning. From the research that has been conducted in two cycles of the first cycle of the activities of teachers percentage of 87.5% to93.75% in the second cycle with excellent category, student activities first cycle of 82.5% to 90% in the second cycle with very good categories , and student learning outcomes on the second cycle increased by 11.7 points (17.26%) from the first cycle to 79.5. It can be concluded that the cooperative learning model type of Jigsaw Can Improve Mathematics Learning Outcomes.Â Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Hasil Belajar Matematika pada Siswa Kelas V Sekolah Dasar Kecamatan Pasir Penyu. Penelitian ini bertujuan untuk meningkatkan hasil belajar matematika siswa kelas V SD Negeri 012 Candirejo Kecamatan Pasir Penyu melalui penerapan model pembelajaran Kooperatif tipe Jigsaw. Subjek penelitian ini adalah siswa kelas V SD Negeri 012 Candirejo Tahun Ajaran 2011/2012, dengan jumlah siswa 30 orang, yang terdiri dari 19 orang siswa lakilaki dan 11 orang siswa perempuan. Instrumen penelitian yang digunakan adalah lembar tes hasil belajar matematika, Lembar Pengamatan Aktivitas Guru dan Lembar Pengamatan Aktivitas Siswa. Teknik pengumpulan dan analisis data diperoleh dari analisis deskripstif aktivitas guru, aktivitas siswa, dan hasil belajar matematika siswa. Dari penelitian yang telah dilakukan dalam 2 siklus aktivitas guru siklus I persentase sebesar 87,5% menjadi 93,75% di siklus II dengan kategori sangat baik, aktivitas siswa siklus I sebesar 82,5% menjadi 90% di siklus II dengan kategori sangat baik, dan hasil belajar siswa pada siklus II meningkat sebesar 11,7 poin (17,26%) dari siklus I menjadi 79,5. Dapat disimpulkan bahwa Model Pembelajaran Kooperatif Tipe Jigsaw dapat Meningkatkan Hasil Belajar Matematika.